Digital Strategy Model in Strengthening Brand Image to Maintain Customer Loyalty (Case Study on Umrah and Hajj Travel Agency) - Suryawan, Ryan Firdiansyah; Kamsariaty, Kamsariaty; Perwitasari, Erni Pratiwi; Maulina, Evaf; Maghfuriyah, Alfi; Susilowati, Tri (East Asian Journal of Multidisciplinary Research, 2023)
The aim of this paper is to provide an overview of literature on digital strategy, brand image, and customer loyalty, contributing a strengthened perspective to this discourse. This paper employs a qualitative methodology, utilizing a literature review model based on findings from papers related to the variables within this study over the past eight years. The outcomes of this paper aim not only to reinforce existing implementation findings but also to contribute to and enrich the research field. The Digital Strategy Model has proven to be a valuable asset for Umrah and Hajj travel agencies in shaping brand image and maintaining customer loyalty. As the digital landscape evolves, a commitment to innovation, personalization, and customer trust will be crucial for sustained success in this competitive industry. Implementing these recommendations, Umrah and Hajj travel agencies can optimize their digital strategies, ensuring a holistic and customer-centric approach that fosters brand loyalty and satisfaction in the digital era.